Chalcogen Bond versus Weak Hydrogen Bond: Changing Contributions in Determining the Crystal Packing of [1,2,5]-Chalcogenadiazole-Fused Tetracyanonaphthoquinodimethanes - Ishigaki, Yusuke; Asai, Kota; Shimajiri, Takuya; Akutagawa, Tomoyuki; Fukushima, Takanori; Suzuki, Takanori (Organic Materials, 2021)
The crystal structures of a series of tetracyanonaphthoquinodimethanes fused with a selenadiazole or thiadiazole ring revealed that their molecular packing is determined mainly by two intermolecular interactions: chalcogen bond (ChB) and weak hydrogen bond (WHB). ChB between Se and a cyano group dictates the packing of selenadiazole derivatives, whereas the S-based ChB is much weaker and competes with WHB in thiadiazole analogues. This difference can be explained by different electrostatic potentials as revealed by density functional theory calculations. A proper molecular design that weakens WHB can change the contribution of ChB in determining the crystal packing of thiadiazole derivatives.
Keywords: crystal engineering; weak hydrogen bonds; chalcogen bonds; chalcogenadiazoles; tetracyanoquinodimethanes; X-ray analysis